Hemostasis mechanism and applications of N-alkylated chitosan sponge - Huang, Y.; Feng, L.; Zhang, Y.; He, L.; Wang, C.; Xu, J.; Wu, Jian-Ping; Kirk, T.; Guo, R.; Xue, W. (2017)
Copyright © 2017 John Wiley & Sons, Ltd. Chitosan (CHI) is a versatile biological material that is well known for its hemostatic properties. This preliminary study evaluated several self-assembling hydrophobically modified chitosan (HM–CHI) sponges to determine their efficacy on hemostasis. Fourier transform infrared (FT-IR) spectroscopy was used to determine the successful graft of dodecyl groups onto the nitrogen atoms of CHI molecules. A platelet aggregation assay revealed that HM–CHI accelerated the platelet aggregation rate. Fluorescence spectroscopy showed that the HM–CHI changed the structure of fibrinogen in blood. Activated partial thromboplastin time, prothrombin time, fibrinogen time, and thromboelastographic assays were used to explore the effect of HM–CHI on the autologous blood coagulation pathway. Finally, a hemostatic sponge was made with HM–CHI and freeze-dried zeolite composite film and was applied to the rat femoral artery hemostasis model. A hemostasis time of 86 ± 5 sec was achieved, which was significantly better than the one composed with pure CHI. The experimental results of the HM–CHI hemostatic materials are inspiring and will encourage the research and development of such materials. HM–CHI may be a strong candidate as a safe and effective hemostatic material. Copyright © 2017 John Wiley & Sons, Ltd.